2014
DOI: 10.3892/ijmm.2014.1940
|View full text |Cite
|
Sign up to set email alerts
|

miR-96 functions as a tumor suppressor gene by targeting NUAK1 in pancreatic cancer

Abstract: microRNA-96 (miR-96) is known to be downregulated in pancreatic cancer. The overexpression of miR-96 in MIA PaCa-2 pancreatic cancer cells has been shown to inhibit cell proliferation, migration and invasion; however, the mechanisms involved have not yet been fully elucidated. Novel (nua) kinase family 1 (NUAK1) functions as an oncogene in non‑small cell lung cancer (NSCLC), melanoma, glioma, breast cancer, hepatocellular carcinoma and pancreatic cancer. In this study, firstly, we demonstrate that NUAK1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…However, some studies suggested that miR‐96 might play an unusual role in pancreatic cancer. According to the studies of Yu et al and Huang et al, down‐regulation of miR‐96 was found in pancreatic cancer and miR‐96 overexpression inhibited cell proliferation and migration . In our study, we verified the low expression of miR‐96 and its tumor‐suppressive function in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 79%
“…However, some studies suggested that miR‐96 might play an unusual role in pancreatic cancer. According to the studies of Yu et al and Huang et al, down‐regulation of miR‐96 was found in pancreatic cancer and miR‐96 overexpression inhibited cell proliferation and migration . In our study, we verified the low expression of miR‐96 and its tumor‐suppressive function in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 79%
“…Many of the differentially expressed protein-coding genes play roles in carcinogenesis (e.g. GAGE12J, VWA2, NUAK1, and MGAT4C), consistent with the transcriptional differences we identified between the NTF2 low and NTF2 high dox+ cell lines (Chen et al, 2013;Demichelis et al, 2012;Gonzalez et al, 2018;Huang et al, 2014).…”
Section: Identification Of Differentially Expressed Genes In Cells Exsupporting
confidence: 83%
“…In the majority of the tumors, miR-96 acts as an oncogene to promote the proliferation and invasion of cancer cells by inhibiting transcription factor FOXO1 (24), FOXO3a (25), tumor suppressor protein RECK (26) and metastasis suppressor protein MTSS1 (27). However, in pancreatic cancer, miR-96 functions as a tumor suppressor by targeting HERG1 and NUAK1 (28,29).…”
Section: Discussionmentioning
confidence: 99%